High-resolution sampling of beam-driven plasma wakefields - S. Schröder (Nature Portfolio, 2020)
Controlled particle acceleration in plasmas requires precise measurements of the excited wakefield. Here the authors report and demonstrate a high-resolution method to measure the effective longitudinal electric field of a beam-driven plasma-wakefield accelerator.